Prophet Hazrat Muhammad’s S.A.W Personal Names; Approaches of Contemporary Orientalists - Aziz, Asma; dduja , Kashaf u (Journal of Quranic and Social Studies, 2022)
In the sixteen to twenty-first centuries a number of Seerah books were written in the aspect of anti-Islamic view. Orientalists started to research on the Prophet Muhammad S.A.W different aspects of life. They started their biased research to fulfill their missionary aims. In that situation, the orientalists of the mid-nineteenth to the twenty-first century had changed their vision towards Islam and Prophet Muhammad’s S.A.W Seerah as well. These orientalists are less biased and show a soft image of Islam and Prophet Muhammad’s S.A.W Seerah. They show their positive face towards the East. Prophet Muhammad S.A.W carries an abundance of attributive names Asmā’u ’n-Nabiyy which are given on His S.A.W noble characteristics and also Allah Almighty calls his beloved Prophet S.A.W with different epithets. The main focus of this research work is to explore the approaches of orientalists and somehow clear the doubts of orientalists and western scholars of the modern age in regard to Prophet Muhammad’s S.A.W pious names.